Peran Dukungan Organisasi pada Karyawan yang Memiliki Kecemasan di Masa Pandemi Covid 19 - Diniprilia, Mita; Rostiana (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2024)
At the beginning of 2020, more precisely in March, the world was shaken by the Corona Virus, which is better known as Covid-19. The corona virus first started to enter Indonesia in the city of Depok, West Java and continued to spread throughout other areas of Indonesia. This virus has a big impact on various aspects of human life, because residents are required to stay at home and do everything at home so as not to become infected with the Covid virus. As a result of the Covid-19 case, the Indonesian government has made various efforts to break the chain of spread of Covid-19, one of which is the policies recommended by the government for companies to implement, namely the implementation of employees working from home or working from office while still implementing the health protocols that have been previously arranged. It is hoped that working employees will continue to do good work for the company, even though there will be anxiety about working in the midst of a pandemic. Researchers used anxiety as a moderator by dividing high anxiety and low anxiety. It is hoped that the condition of employees with high or low levels of anxiety will play a role in the influence of perceptions of organizational support on work performance. The number of samples is 100 people. The data collection technique is a quantitative research method. The results of this research are perceptions of participating organizations' support for work among employees with low levels of anxiety. However, when anxiety levels are high, perceptions of organizational support do not contribute to work.